The entropy production of Ornstein–Uhlenbeck active particles: a path integral method for correlations. (23rd May 2019) - Caprini, Lorenzo; Marconi, Umberto Marini Bettolo; Puglisi, Andrea; Vulpiani, Angelo
Abstract: By employing a path integral formulation, we obtain the entropy production rate for a system of active Ornstein–Uhlenbeck particles (AOUP) both in the presence and in the absence of thermal noise. The present treatment clarifies some contraddictions concerning the definition of the entropy production rate in the AOUP model, recently appeared in the literature. We derive explicit formulas for three different cases: overdamped Brownian particle, AOUP with and without thermal noise. In addition, we show that it is not necessary to introduce additional hypotheses concerning the parity of auxiliary variables under time reversal transformation. Our results agree with those based on a previous mesoscopic approach.